Scientific, Systematic Issues in the Study of Uzbek Folklore - Gulirukhsar Jorayeva; Shahodatbоnu Imomnazarova (Researchparks Publishing, 2022)
In this article, one of the most ancient life-giving national values, folklore art and Uzbek folk music, is discussed in the process of studying the issues of scientificity and systematicity.